Silicon Thin-Film Solar Cells. (17th December 2007) - Beaucarne, Guy
Abstract : We review the field of thin-film silicon solar cells with an active layer thickness of a few micrometers. These technologies can potentially lead to low cost through lower material costs than conventional modules, but do not suffer from some critical drawbacks of other thin-film technologies, such as limited supply of basic materials or toxicity of the components. Amorphous Si technology is the oldest and best established thin-film silicon technology. Amorphous silicon is deposited at low temperature with plasma-enhanced chemical vapor deposition (PECVD). In spite of the fundamental limitation of this material due to its disorder and metastability, the technology is now gaining industrial momentum thanks to the entry of equipment manufacturers with experience with large-area PECVD. Microcrystalline Si (also called nanocrystalline Si) is a material with crystallites in the nanometer range in an amorphous matrix, and which contains less defects than amorphous silicon. Its lower bandgap makes it particularly appropriate as active material for the bottom cell in tandem and triple junction devices. The combination of an amorphous silicon top cell and a microcrystalline bottom cell has yielded promising results, but much work is needed to implement it on large-area and to limit light-induced degradation. Finally thin-film polysilicon solar cells, with grain size in the micrometer range, has recently emerged as an alternative photovoltaic technology. The layers have a grain size ranging from 1 μ m to several tens of microns, and are formed at a temperature ranging from 600 to more than1000 ∘ C . Solid Phase Crystallization has yielded the best results so far but there has recently been fast progress with seed layer approaches, particularly those using the aluminum-induced crystallization technique.